The significance of retroperitoneal-first laparoscopic approach (Retlap) using the innermost layer approach to preserve the celiac axis in laparoscopic distal pancreatectomy for pancreatic body cancer close to the arterial wall. (June 2021) - Kiguchi, Gozo; Sugioka, Atsushi; Kato, Yutaro; Uyama, Ichiro
Highlights: Retlap was applied for laparoscopic distal pancreatectomy with lymphadenectomy. The patient had a pancreatic body cancer close to arterial wall to be preserved. Innermost layer approach to expose arterial wall beneath vasa vasorum was applied. Retlap and innermost layer approach was useful to obtain an adequate margin. This video demonstrates detailed concept and procedure of innermost layer approach.